Potensi dan Upaya Pemanfaatan Air Tanah untuk Meningkatkan Kehidupan Sosial Ekonomi Petani di Desa Lise Kabupaten Sidenreng Rappang - Tannaim, Anida; Hasriyanti, Hasriyanti; Nasiah, Nasiah (LaGeografia, 2019)
This study aims to determine the potential and efforts to utilize groundwater, the comparison of production result between irrigation and rainfed farmers and how the socio-economic life of farmers in Lise’ village, Pancalautang sub district, Sidenreng Rappang district. This research is quantitative descriptive. Data collection is done through observation, questionnaires and documentation. With data processing techniques with descriptive statistical analysis and inferential statistical analysis. The population in this study were 400 families, while the sample of this study was 80 families. Efforts to utilize ground water in Lise village for agricultural development have been carried out by the Ministry of PUPR through Groundwater Utilization (PAT) in the Central Pompengan-Jeneberang River Basin by drilling deep wells and shallow wells. The existence of groundwater irrigation in the village of Lise can help farmers to increase the yield of rice every year, where the comparison between the production of farmers in the irrigation group and rain fed groups with the difference in the difference is 0,8200 to 40,000. As for the socio-economic life of farmers in the village Lise 'can be said to be good. This is because most people choose to become farmers both cultivators and others. Farming experience for farmers affects land processing due to the amount of knowledge that has been applied. And affect the amount of production so that it can increase farmers' income.